Carbon-phenolic ablative materials for re-entry space vehicles: plasma wind tunnel test and finite element modeling. (15th January 2016) - Paglia, L.; Tirillò, J.; Marra, F.; Bartuli, C.; Simone, A.; Valente, T.; Pulci, G.
Abstract: A lightweight carbon-phenolic ablator, with a density of 0.5 g/cm 3, designed to be used as a thermal protection system for a re-entry space vehicle, was manufactured by infiltration of a carbon felt with a phenolic resin. A sample of this ablative material was tested in a Plasma Wind Tunnel (PWT) facility, simulating erosion and heat flux conditions consistent with an orbital reentry. The surface temperature of the test article was monitored during the PWT test. Microstructural and microtomographic analyses were carried out on the tested sample to investigate the effect of the high heat flux exposure on the composite material, by measuring the amount of ablation and the depth of pyrolyzation. Moreover a finite element model was implemented in order to rebuild the PWT test. Very encouraging results were obtained in terms of surface insulation capacity and surface recession. The pyrolysis and erosion of the ablator was simulated by implementing a complex finite element model, with results in very good agreement with experimental evidences. Graphical abstract: Highlights: A lightweight carbon-phenolic ablative material was manufactured with a density of 0.5 g/cm 3 . The ablative material was tested in a plasma wind tunnel facility at a maximum heat flux level of 3.2 MW/m 2 . Post-test analyses were carried out by means of microtomography and SEM micrographs. A finite element model was developed to simulate the PWT test taking into account both ablation and pyrolysis phenomena.